2022
DOI: 10.1007/s00330-022-08719-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of image-guided ablation and laparoscopic partial nephrectomy for T1 renal cell carcinoma

Abstract: Objective To compare long-term outcomes and peri-operative outcomes of image-guided ablation (IGA) and laparoscopic partial nephrectomy (LPN). Material and methods This is a retrospective cohort study of localised RCC (T1a/bN0M0) patients undergoing cryoablation (CRYO), radio-frequency ablation (RFA), or LPN at our institution from 2003 to 2016. Oncological outcomes were compared using Cox regression and log-rank analysis. eGFR changes were compared using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 32 publications
0
34
1
Order By: Relevance
“…For cT1b, the results were: 77.78%, 92.68%, 93.8%, 93.7% for OS, RFS, DSS and MFS, respectively. Which, when compared to the work of Aron et al 2010 [ 49 ] with OS, RFS, DSS and MFS results of 84%, 87%, 89% and 89% for cT1a, presents results in favor of the more recent work [ 15 , 16 , 26 , 27 , 28 , 34 ], presented in our review.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…For cT1b, the results were: 77.78%, 92.68%, 93.8%, 93.7% for OS, RFS, DSS and MFS, respectively. Which, when compared to the work of Aron et al 2010 [ 49 ] with OS, RFS, DSS and MFS results of 84%, 87%, 89% and 89% for cT1a, presents results in favor of the more recent work [ 15 , 16 , 26 , 27 , 28 , 34 ], presented in our review.…”
Section: Discussioncontrasting
confidence: 60%
“…Wośkowiak et al [ 48 ] pointed out that data on long term follow-up of CA and RFA are limited. We managed to find results [ 16 , 34 ] on 10 year survival with mean OS, RFS, DSS, MFS of 72.95%, 80.65%, 97%, 100%, respectively for CA and 5 year [ 26 , 27 , 34 ] for RFA with mean OS, RFS, DSS, MFS of 87.8%, 95.8%, 98.13% and 97.07%, respectively, which are superior to the OS, RFS, DSS and MFS results of 75.8%, 93.5%, 97.9% and 87.7% in a study [ 50 ] mentioned in an earlier review [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MFS rates are 97.9% (95% CI 94.4–99.2%) at both five and ten years. Full oncological outcomes, in comparison to partial nephrectomy, have been reported previously [ 2 ].…”
Section: Resultsmentioning
confidence: 72%
“…A recent systematic review and meta-analysis comparing the ablative therapies and partial nephrectomy showed comparable oncological outcomes, superior renal function preservation and superior complication rates in ablation patients in comparison to partial nephrectomy patients [ 1 ]. Similarly, a retrospective study with 10 years of experience also showed comparable oncological outcomes and superior renal function in patients undergoing IGA compared to PN [ 2 ]. In specifically selected patients, active surveillance may be a viable option [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published evidence has shown improving oncological outcomes in thermal ablation for the management of T1a renal tumours. There are now multiple long term singlecentre studies [6][7][8][9][10] and multiple larger population based studies [11][12][13] that support use of thermal ablation for the management of T1a tumours. Two prospective studies by Wah et al 8 in165 patients and Leveillee et al 7 in 274 patients show that RFA is clinically effective and safe with a low recurrence rate and high overall survival (OS) (Table 1).…”
Section: Oncological Outcomes For T1a Tumoursmentioning
confidence: 99%